PENGARUH PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PASIEN HIPERTENSI RAWAT JALAN DI RUMAH SAKIT ANWAR MEDIKA - Rosi Maya Andriani; Khurin In Wahyuni; Puspita Raras Anindita (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
This study aims to determine the satisfaction of outpatient hypertension patients at Anwar Medika Hospital and to determine the effect of pharmaceutical services on outpatient hypertension patient satisfaction at Anwar Medika Hospital. This research method is an observational research with a descriptive research design using quantitative analysis. This research at Anwar Medika Hospital was conducted in March 2020. This research approach uses a survey approach where the data collection process is carried out by distributing questionnaires and interviews to respondents. For easy data processing, SPSS version 20 was used. The results of the study were 200 respondents. This study concluded that the respondents expressed very dissatisfaction with 1.2%, the respondents stated that they were not satisfied with 4.8%, the respondents stated that they were satisfied with 27.9%, the respondents stated that they were very satisfied with 66.2%. The effect of the level of pharmaceutical services on the satisfaction of hypertensive patients is y = 35.869 + 0.460x.